Effect of Rh Doping on Optical Absorption and Oxygen Evolution Reaction Activity on BaTiO3 (001) Surfaces - Inerbaev, Talgat M.; Abuova, Aisulu U.; Zakiyeva, Zhadyra Ye.; Abuova, Fatima U.; Mastrikov, Yuri A.; Sokolov, Maksim; Gryaznov, Denis; Kotomin, Eugene A. (MDPI, 2024)
In the present work, we investigate the potential of modified barium titanate (BaTiO3), an inexpensive perovskite oxide derived from earth-abundant precursors, for developing efficient water oxidation electrocatalysts using first-principles calculations. Based on our calculations, Rh doping is a way of making BaTiO3 absorb more light and have less overpotential needed for water to oxidize. It has been shown that a TiO2-terminated BaTiO3 (001) surface is more promising from the point of view of its use as a catalyst. Rh doping expands the spectrum of absorbed light to the entire visible range. The aqueous environment significantly affects the ability of Rh-doped BaTiO3 to absorb solar radiation. After Ti→Rh replacement, the doping ion can take over part of the electron density from neighboring oxygen ions. As a result, during the water oxidation reaction, rhodium ions can be in an intermediate oxidation state between 3+ and 4+. This affects the adsorption energy of reaction intermediates on the catalyst’s surface, reducing the overpotential value. © 2024 by the authors. --//-- This is an open-access article Inerbaev, T.M.; Abuova, A.U.; Zakiyeva, Z.Y.; Abuova, F.U.; Mastrikov, Y.A.; Sokolov, M.; Gryaznov, D.; Kotomin, E.A. Effect of Rh Doping on Optical Absorption and Oxygen Evolution Reaction Activity on BaTiO3 (001) Surfaces. Molecules 2024, 29, 2707. https://doi.org/10.3390/molecules29112707 published under the CC BY 4.0 licence.
This work was carried out with the financial support of the Ministry of Science and Higher Education of the Republic of Kazakhstan: AP14869492 \u201CDevelopment of nanocrystalline metal oxide catalysts for hydrogen production\u201D. EK thanks M-Era.NET project HetCat. The calculations were partly performed at the High-Performance Computing Center Stuttgart (HLRS) within the project DEFTD 12939. YM and DG thank the Latvian Council of Science, project No. lzp-2021/1-0203. The work by T.M.I. was performed under the state assignment of GEOKHI RAS. T.I. also thanks the Center for Computational Materials Science (IMR, Tohoku University) for providing access to the supercomputing system used to perform the simulations. The Institute of Solid-State Physics, University of Latvia (Latvia), as a Center of Excellence, has received funding from the European Union Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-Teaming Phase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; electrocatalysis; electrode materials; energy storage and conversion; photocatalysis; water splitting